Thatcher's Britain: A New Take on an Old Illusion. (December 2014) - Johnston, Patrick; Baker, Daniel H; Stone, Rob; Kaufman, Jordy
The Thatcher Illusion is generally discussed as a phenomenon related to face perception. Nonetheless, we show that compellingly strong Thatcher Effects can be elicited with nonface stimuli, provided that the stimulus set has a familiar standard configuration and a canonical view. Apparently, the Thatcher Illusion is not about faces, and nor is it about Thatcher. It just might, however, be about Britain.